Best Practice Halal Integrity Management In The Logistic Chain Scheme: Analysis Of Opportunities And Challenges - Rizki, Darlin; Hamzah, Moh.; Fakhiroh, Zakiyatul; Hendri, Darwin (Journal of Islamic Economic Laws, 2023)
Nowadays, consumers are increasingly aware and concerned about halal status, and activities in the supply chain are truly halal guaranteed for them to buy. This article aims to explore the development of halal logistics, analyze the opportunity and challenge factors in its development stage, and create a best practice scheme to realize halal integrity. This research method uses a Systematic Literature Review (SLR) using secondary data from several previous studies discussing halal logistics and halal integrity in the supply chain. From this study, it is known that countries in Southeast Asia have shown a positive response to the existence of a halal logistics scheme as an innovation in the supply chain. Several opportunities known for the development of halal logistics mainly lie in the high demand for halal products, the positive growth of the sharia economy, the use of information technology, and the strengthening of the halal ecosystem. Meanwhile, regarding challenges, there needs to be a special regulation regulating halal logistics, common stakeholder knowledge about halal, a need for more experts and researchers, and the absence of a particular infrastructure that handles halal products. In the end, the author develops a halal integrity scheme in the supply chain with a logistics management approach. This article can better understand halal integrity in the supply chain. Further research can empirically test the relationship between logistics management and halal integrity.